Assessment of Customers' Perception of Social Responsibility of Trade Business - Mayorova, Elena Aleksandrovna; Lapitskaya, Natalia Vladimirovna (International Journal of Economics and Financial Issues, 2016)
The relevance of the topic is determined by high activity of the modern trade business in corporate social responsibility. It is caused by the increased competition, necessity to comply with international norms and standards, increased exactingness of customers to the social aspects of trade companies' work. The article is aimed at assessing the customers` perception of social responsibility of trade business and development of recommendations to trade business units on implementation of the corporate social responsibility concept. To achieve the set goal, a survey among the customers of Moscow region was conducted. The statistical and the graphic methods were used in processing the results of the survey. The article assesses a general attitude of customers to corporate social responsibility of trade business; it reveals the most and the least significant components of social responsibility for customers; awareness of customers about social trade business activity was analyzed; the article includes the most effective ways of awareness raising among the customers on the work of the trade organizations in corporate social responsibility. Practical significance of the obtained results is conditioned by the fact that the implementation of corporate social responsibility concept in accordance with the expectations and preferences of customers will increase economic efficiency of trade business units; it will contribute to the society life improvement as well. Keywords: social responsibility, trade, trade organization, customers, Moscow region. JEL Classifications: L81, M14.